FOLKLORE TRADITIONS IN THE POET'S POETRY (TAMADDUN NURI JURNALI, 2024)
This article discusses the art of folklorisms used in the work of the talented poet Eshqobil Shukur and their types. The topic of the article is explained using examples, based on scientific and theoretical ideas.